Applying the science impact framework to understand real-world applications and impacts of ICESat and ICESat-2 data on decision-making - Siobhan L. Light; Molly E. Brown; Aimee R. Neeley; Thomas A. Neumann (Remote Sensing Applications: Society and Environment, 2025)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Amphetamine alters an EEG marker of reward processing in humans and mice - James F. Cavanagh; Sarah L. Olguin; Jo A. Talledo; Juliana E. Kotz; Benjamin Z. Roberts; John A. Nungaray; Joyce Sprock; David Gregg; Savita G. Bhakta; Gregory A. Light; Neal R. Swerdlow; Jared W. Young; et al. (Psychopharmacology, 2022)

Subzero, saline incubations of Colwellia psychrerythraea reveal strategies and biomarkers for sustained life in extreme icy environments - Miranda C. Mudge; Brook L. Nunn; Erin Firth; Marcela Ewert; Kianna Hales; William E. Fondrie; William S. Noble; Jonathan Toner; Bonnie Light; Karen A. Junge (Environmental Microbiology, 2021)
Summary Colwellia psychrerythraea is a marine psychrophilic bacterium known for its remarkable ability to maintain activity during long‐term exposure to extreme subzero temperatures and correspondingly high salinities in sea ice. These microorganisms must have adaptations to both high salinity and low temperature to survive, be metabolically active, or grow in the ice. Here, we report on an experimental design that allowed us to monitor culturability, cell abundance, activity and proteomic signatures of C. psychrerythraea strain 34H ( Cp 34H) in subzero brines and supercooled sea water through long‐term incubations under eight conditions with varying subzero temperatures, salinities and nutrient additions. Shotgun proteomics found novel metabolic strategies used to maintain culturability in response to each independent experimental variable, particularly in pathways regulating carbon, nitrogen and fatty acid metabolism. Statistical analysis of abundances of proteins uniquely identified in isolated conditions provide metabolism‐specific protein biosignatures indicative of growth or survival in either increased salinity, decreased temperature, or nutrient limitation. Additionally, to aid in the search for extant life on other icy worlds, analysis of detected short peptides in −10°C incubations after 4 months identified over 500 potential biosignatures that could indicate the presence of terrestrial‐like cold‐active or halophilic metabolisms on other icy worlds.

Red imported fire ant (Solenopsis invicta) aggression influences the behavior of three hard tick species - MacKenzie K. Kjeldgaard; Oona M. Takano; Alison A. Bockoven; Pete D. Teel; Jessica E. Light; Sarah A. Hamer; Gabriel L. Hamer; Micky D. Eubanks (Experimental and Applied Acarology, 2019)

Patterns of frontoparietal activation as a marker for unsuccessful visuospatial processing in healthy aging - Lauren L. Drag; Sharee N. Light; Scott A. Langenecker; Kathleen E. Hazlett; Elisabeth A. Wilde; Robert Welsh; Brett A. Steinberg; Linas A. Bieliauskas (Brain Imaging and Behavior, 2016)

Mineralization ratios of nitrogen and phosphorus from decomposing litter in temperate versus tropical forests - Alison R. Marklein; Joy B. Winbourne; Sara K. Enders; David J. X. Gonzalez; Tiff L. van Huysen; Jorge E. Izquierdo; Derrick R. Light; Daniel Liptzin; Kimberley E. Miller; Scott L. Morford; Robert A. Norton; Benjamin Z. Houlton (Global Ecology and Biogeography, 2016)
Aim Terrestrial ecosystems sequester about 25% of anthropogenic CO 2 emissions annually; however, nitrogen ( N ) and phosphorus ( P ) limitation of plant productivity and microbial functioning could curtail this key ecosystem service in the future. Our aim is to address variations in nutrient resupply during decomposition – especially whether the N : P ratio of nutrient recycling via mineralization varies within and across diverse forest biomes. Location Global forest ecosystems. Methods We compiled data on in situ litter decomposition experiments (leaf, wood and root) from the primary literature to examine the relationships between net N and P mineralization across temperate versus tropical forests world‐wide. We define net nutrient mineralization ratios as the average N : P released from decomposing substrates at a given ecosystem site. Results We show that net N and P mineralization are strongly correlated within biomes, suggesting strong coupling between N and P recycling in forest ecosystems. The net N : P of leaf‐litter mineralization is higher in tropical forests than in temperate forests, consistent with latitudinal patterns in foliar and leaf‐litter N : P . At the global scale, the N : P of net mineralization tracks, but tends to be lower than that of litter N : P , pointing to preferential P (versus N ) mineralization in forest ecosystems. Main conclusions Our results do not support the view that there is a single, globally consistent mineralization N : P ratio. Instead, our results show that the N : P of net mineralization can be predicted by the N : P of litter, offering a method for incorporating P into global‐scale models of carbon–nutrient–climate interactions. In addition, these results imply that P is scarce relative to microbial decomposer demands in tropical forests, whereas N and P may be more co‐limiting when compared with microbial biomass in the temperate zone.

Evidence for competition between Ixodes scapularis and Dermacentor albipictus feeding concurrently on white-tailed deer - Marcie L. Baer-Lehman; Theo Light; Nathan W. Fuller; Katherine D. Barry-Landis; Craig M. Kindlin; Richard L. Stewart (Experimental and Applied Acarology, 2012)

Swelling-Induced Ca2+ Influx and K+ Efflux in American Alligator Erythrocytes - Alina B. Elperin; Shruti A. Pore; Jordanah M. Evans; Annabel L. Naditz; Douglas B. Light (The Journal of Membrane Biology, 2011)

Isolation and characterization of 17 polymorphic microsatellite loci in the kangaroo mouse, genus Microdipodops (Rodentia: Heteromyidae) - Stacey L. Lance; Jessica E. Light; Kenneth L. Jones; Cris Hagen; John C. Hafner (Conservation Genetics Resources, 2010)

Realistic expectations of prepulse inhibition in translational models for schizophrenia research - Neal R. Swerdlow; Martin Weber; Ying Qu; Gregory A. Light; David L. Braff (Psychopharmacology, 2008)

A pear-derived kairomone with pheromonal potency that attracts male and female codling moth, Cydia pomonella (L.) - Douglas M. Light; Alan L. Knight; Clive A. Henrick; Dayananda Rajapaska; Bill Lingren; Joseph C. Dickens; Katherine M. Reynolds; Ronald G. Buttery; Gloria Merrill; James Roitman; Bruce C. Campbell (The Science of Nature, 2001)

Attractants from Bartlett pear for codling moth, Cydia pomonella (L.), larvae - Alan L. Knight; Douglas M. Light (The Science of Nature, 2001)

Detection of Legionella DNA in Guinea Pig Peripheral Leukocytes, Urine and Plasma by the Polymerase Chain Reaction - L. C. Jennings; S. T. Chambers; D. R. Murdoch; G. J. Light (European Journal of Clinical Microbiology & Infectious Diseases, 1999)